2013
DOI: 10.1109/tpds.2012.97
|View full text |Cite
|
Sign up to set email alerts
|

Scalable and Secure Sharing of Personal Health Records in Cloud Computing Using Attribute-Based Encryption

Abstract: Abstract-Personal health record (PHR) is an emerging patient-centric model of health information exchange, which is often outsourced to be stored at a third party, such as cloud providers. However, there have been wide privacy concerns as personal health information could be exposed to those third party servers and to unauthorized parties. To assure the patients' control over access to their own PHRs, it is a promising method to encrypt the PHRs before outsourcing. Yet, issues such as risks of privacy exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
497
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 973 publications
(528 citation statements)
references
References 25 publications
1
497
0
1
Order By: Relevance
“…Simulation results showed that their access control is efficient, fine-grained, and scalable. Li et al [9] proposed a novel patient-centric framework and a suite of mechanisms for data access control to PHRs stored in semitrusted servers. To achieve fine-grained and scalable data access control for PHRs, they leveraged attribute-based encryption (ABE) techniques to encrypt each patient's PHR file and exploited multiauthority ABE to guarantee a high degree of patient privacy.…”
Section: Access Controlmentioning
confidence: 99%
“…Simulation results showed that their access control is efficient, fine-grained, and scalable. Li et al [9] proposed a novel patient-centric framework and a suite of mechanisms for data access control to PHRs stored in semitrusted servers. To achieve fine-grained and scalable data access control for PHRs, they leveraged attribute-based encryption (ABE) techniques to encrypt each patient's PHR file and exploited multiauthority ABE to guarantee a high degree of patient privacy.…”
Section: Access Controlmentioning
confidence: 99%
“…There exists also a number of architectures that employ Attribute-Based encryption (ABE) scheme [14][15][16]19,27]. However, these approaches have several limitations.…”
Section: Existing Approachesmentioning
confidence: 99%
“…So it reduces the key management complexity. In [1][2], both KP-ABE and MA-ABE is used for reducing the key management complexity.…”
Section: Attribute-based Encryption (Abe)mentioning
confidence: 99%
“…In this patients can store their health information on certain web servers. A PHR system allows a patient to create, manage and control their personal health data in centralized place through the web [1]. Each patient has full control over their medical records and they can share the health data with a wide range of users including healthcare providers, family members, friends etc.…”
Section: Introductionmentioning
confidence: 99%